LOW SCIENTIFIC LITERACY OF PHYSICS EDUCATION STUDENTS ON MECHANICAL ENERGY IN EVERYDAY CONTEXTS - Sa'diyah, Ervi Khalimatus; Putranta, Himawan (PENSA E-JURNAL: PENDIDIKAN SAINS, 2026)
Scientific literacy is a key competency for prospective physics teachers, particularly in connecting physics concepts to everyday phenomena. This study aims to examine the level of scientific literacy among Physics Education students on mechanical energy topics using real-life contexts. A descriptive quantitative approach was applied to a group of 30 undergraduate students enrolled in a physics teacher education program. Scientific literacy was assessed through context-based tasks focused on everyday mechanical energy phenomena. The results indicate that the average scientific literacy score was 37.33, placing it in the low category. In total, more than 60% of the students demonstrated low to very low levels of scientific literacy, suggesting that most participants have not yet developed sufficient competence in applying mechanical energy concepts to real-world situations. When analyzed by gender, female students had higher average scores than male students, although their performance was more variable. These findings reveal persistent challenges that prospective physics teachers face in interpreting and applying physics knowledge meaningfully in everyday contexts. The study underscores the importance of integrating context-based and literacy-oriented instructional approaches in physics teacher education programs to better equip future teachers with the skills necessary to promote scientific literacy among secondary school students.